Staged reconstruction brachytherapy has lower overall cost in recurrent soft-tissue sarcoma - Naghavi, Arash O.; Gonzalez, Ricardo J.; Scott, Jacob G.; Kim, Youngchul; Abuodeh, Yazan A.; Strom, Tobin J.; Echevarria, Michelle; Mullinax, John E.; Ahmed, Kamran A.; Harrison, Louis B.; Fernandez, Daniel C. (Journal of Contemporary Brachytherapy, 2017)
Purpose : Adjuvant brachytherapy (AB) with immediate (IR) and staged reconstruction (SR) are distinct treatment modalities available for patients with recurrent soft tissue sarcoma (STS). Although SR may offer local control and toxicity benefit, it requires additional upfront procedures, and there is no evidence that it improves overall survival. With the importance of value-based care, our goal is to identify which technique is more cost effective. Material and methods : A retrospective review of 22 patients with recurrent extremity STS treated with resection followed by AB alone. Hospital charges were used to compare the cost between SR and IR at the time of initial treatment, at 6-month intervals following surgery, and cumulative cost comparisons at 18 months. Results : Median follow-up was 31 months. Staged reconstruction (n = 12) was associated with an 18-month local control benefit (85% vs. 42%, p = 0.034), compared to IR (n = 10). Staged reconstruction had a longer hospital stay during initial treatment (10 vs. 3 days, p = 0.002), but at 18 months, the total hospital stay was no longer different (11 vs. 11 days). Initially, there was no difference in the cost of SR and IR. With longer follow-up, cost eventually favored SR, which was attributed primarily to the costs associated with local failure (LF). On multivariate analysis, cost of initial treatment was associated with length of hospital stay (~$4.5K per hospital day, p < 0.001), and at 18 months, the cumulative cost was ~175K lower with SR (p = 0.005) and $58K higher with LF (p = 0.02). Conclusions : In recurrent STS, SR has a longer initial hospital stay when compared to IR. At 18 months, SR had lower rates of LF, translating to lower total costs for the patient. SR is the more cost-effective brachytherapy approach in the treatment of STS, and should be considered as healthcare transitions into value-based medicine.